Pemanfaatan Gofood (Gojek) Mengatasi Risiko Konsinyasi dan Percepatan Arus Kas UMKM Sektor Kuliner Purwakarta: Pengabdian - Nisa Aprilia Sapitri; Elih Herawati; Restu Rillahi Sahwal; Dedeng Abdul Gani Amrullah (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This community service activity focused on Dapur Dhyandra, a culinary MSME in Purwakarta that produces snacks, which faced operational challenges due to its reliance on a consignment system. This reliance led to product inventory buildup and negatively impacted its capital turnover. To address this obstacle and limited market reach, this program aimed to assist business owners in expanding their digital market by creating and activating GoFood (Gojek) accounts. Implementation methods included observation, account registration, and comprehensive training on digital operational management. The results showed that the business owners successfully mastered the platform, opened new sales channels, and gained insights that enabled marketing strategy diversification to reduce reliance on consignment. This digitalization implementation had a direct positive impact in the form of market expansion and increased potential capital turnover, while also supporting Dapur Dhyandra's modernization, enabling this culinary business to maintain its competitiveness in the digital era.